Unexpected diversity and novel lineages in the cosmopolitan genus Nanomia (Cnidaria: Siphonophorae: Physonectae) - Hosia, Aino; Martell, Luis; Mańko, Maciej K.; Haddock, Steven H. D.; Haberlin, Damien; Mapstone, Gillian M. (Frontiers in Marine Science, 2024)
Integrated use of molecular and morphological methods reveals unexpected diversity in the cosmopolitan siphonophore genus Nanomia. Species delimitation analyses based on COI and 16S sequences suggest up to three distinct lineages in addition to the previously accepted Nanomia bijuga (Delle Chiaje, 1844) and N. cara A. Agassiz, 1865. Here, we describe the North Pacific Nanomia septata sp. n., previously confused with both N. cara and N. bijuga, and provide improved morphological characters for the identification of these three Nanomia species. Phylogenetic analyses suggest two additional, hitherto undescribed clades from Japanese and Chinese waters, respectively, but the lack of morphological material prevents describing these putative species. The geographic distribution of molecularly and/or morphologically verified observations confirm a warm circumglobal distribution for N. bijuga and a boreal North Atlantic distribution for N. cara. Interestingly, four distinct lineages occur in the North Pacific, sometimes in close proximity. These contrasting patterns of distribution raise questions about pelagic speciation processes. Nanomia septata sp. n.: urn:lsid:zoobank.org:act:DAF15EA3-AFEA-4AE8-984F-BDFBCFE7E514 urn:lsid:zoobank.org:pub:478049FC-F672-4D34-ABAE-CF4345EC64D7